Relevansi Kemampuan Pengolahan Perangkat Lunak Corel Draw 13 dengan Kualitas Tampilan Desain Busana Berformat Digital - Wiana, Winwin (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
This study aims at determining the relevance of skills in processing software Corel Draw 13, digital format fashion design result, as well as the relevance between the two variables under study. Population and sample of this study are 31 students of Fashion Design Management, Fashion Studies Program, PKK FPTK UPI, class 2005 and 2006. The method used is descriptive correlational method. Data collection is conducted by assessing the tasks in Applied Computer courses and digital format fashion design task Fashion Design class. The data is then processed using statistical calculation/analysis. The results show that participants tend to have very high ability in processing software Corel Draw 13. The qualities of digital format fashion design that are created are mostly at very high criteria. In addition, coefficient of determination obtained in level of confidence 95% and 99% obtains is 81%. The results indicate that there is a positive and significant functional relationship between the ability of processing software Corel Draw 13 and quality of digital format fashion designs created.